Development of a solar radiation sensor system with pyranometer - Muchamad Rizky Nugraha; Andi Adriansyah (International Journal of Electrical and Computer Engineering (IJECE), 2022)
Solar energy is a result of the nuclear fusion process in the form of a series of thermonuclear events that occur in the Sun's core. Solar radiation has a significant impact on the lives of all living things on earth. The uses, as mentioned earlier, are when the solar radiation received requires a certain amount and vice versa. As a result, a more accurate instrument of solar radiation is required. A specific instrument is typically used to measure solar radiation parameters. There are four solar radiation parameters: diffusion radiation, global radiation, direct radiation, and solar radiation duration. Thus, it needs to use many devices to measure radiation data. The paper designs to measure all four-radiation data by pyranometer with particular modification and shading device. This design results have a high correlation with a global standard with a value of R=0.73, diffusion with a value of R=0.60 and a sufficiently strong direct correlation with a value of R=0.56. It can be said that the system is much simpler, making it easier to monitor and log the various solar radiation parameters.